PENDAMPINGAN PEMASARAN PRODUK UMKM OLAHAN SINGKONG MENGGUNAKAN DIGITAL MARKETING - Abdullah, Abdullah; Tri Sumiyanti (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
Impact Current technological developments require society to be able to face the challenges of the times. One of those affected by change is in the economic sector. The growth of society's needs is increasing which requires people to be aware of technology at this time, many consumers are utilizing technology via the internet. The internet is a technological tool that provides very extensive facilities and is easy to access. The development of the times has made people's lifestyles and consumption shift from conventional to online transactions. This community service focuses on understanding and optimizing the marketing of MSMEs in Nongkosawit Village, Gunungpati District, Semarang City, the aim is to make residents more capable and optimize the use of digitalization in marketing their MSME products, seeing the role of digital in the current digital era is very supportive in marketing MSME products in society. In this community service, an R & D approach is used, where the author tries to analyze by participating directly in the field to analyze the problems that exist in society and then map and resolve these problems. We hope that in this service the community and MSME players in Nongkosawit Subdistrict, Gunungpati District, Semarang City can utilize digital marketing to introduce and disseminate MSME products at the local, national and international levels. Keywords : Marketing, UMKM, Digital Marketing